(untitled) (Communications in Mathematical Research, 2019)
In this article, under quite weaker conditions, theorems of Helly's type for (not necessarily finite) family of partially closed half-spaces are presented in both analytic and geometric forms. Examples are also provided to show that these conditions cannot be omitted in general.